Yaḥyā ibn ʿAdī: Treatise on Divine Unity According to the Doctrine of the Christians : Arabic text, English Translation and Commentary - Mandolino, Giovanni (Eastern Christian Texts, 2023)
How do intellectual traditions interact? This is the fundamental question driving this book, which explores a case study set in the early Islamicate world: the Treatise on Divine Unity According to the Doctrine of the Christians by the Christian-Arabic theologian and philosopher Yaḥyā ibn ʿAdī (d. 974). The book attempts to contextualise the treatise and its intellectual environment by exploring the interplay between philosophy, Christian theology and Islam. This volume includes a revised Arabic text of Samir's 2015 edition, collated with the manuscript Tehran, Madrasa-yi Marwī 19, recently discovered by prof. Robert Wisnovsky.